Fernando Peixoto como crítico teatral na imprensa alternativa : jornais Opinião (1973-1975) e Movimento (1975-1979) - Rodrigues, Victor Miranda Macedo (2008)
The present work has as objective to analyze the trajectory of the actor and Brazilian director Fernando Peixoto, as teatral critic, in the alternative press , specifically, in two periodic ones: Opinião, between 1973 and 1975, and Movimento, between 1975 and 1979. We search to understand the character differentiated of the alternative press during the period of the Brazilian military regimen, the heterogeneity of its proposal, its relation with the sectors of opposition of the country and the meaning politician to be part of this journalistic segment. The critical ones of Peixoto, in both the periodicals, are important documents to apprehend strike them that they occurred in the Brazilian theater: the artistic trends in dispute, the new forms of expression and resistance under the sign of the censorship and, mainly, the meaning of the enrollment of the critic for a politically responsible, transforming and conscientious theater of its function in the fight for national and popular aspirations.